Miniaturization of Microstrip Antenna Using Spiral labyrinth Method at Frequency of Work 3.5 GHz - Diah Setiyowati; Syah Alam; Indra Surjati (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Along with the times, communication technology has developed so that it is currently included in the Fifth Generation (5G) Communication System. The 5G communication system is divided into three frequency categories, namely low band, middle band and high band. One of the important devices in the telecommunications sector is the antenna. Antenna serves to send and receive electromagnetic signals at a certain working frequency. Currently, antennas have been completely integrated into the needs of modern society. One type of antenna that can support the needs of today's technology is a microstrip antenna. This antenna has several advantages, especially in its antenna compact design, low profile configuration and affordable manufacturing costs. In this article, a microstrip antenna is designed with the spiral labyrinth  method that works at a frequency of 3.5 GHz for 5G communication system. Propsosed antena designed using RT Duroid R5880 with dielectric constant ( ) 2.2, dielectric loss (loss tan) 0.0009 and thickness (h) 1.57 mm. The simulation results show the reflection coefficient -29.58 dB, VSWR 1.069, gain 6.432 dB at frequency of 3.5 GHz . Spiral labyrinth  has been succesfully reduced patch antenna and enclosure until 22.5%  and 24.8%, respectively.